Chronic vulvar eczema? - Torre, Ana Clara; Subizar, Diana; Gonzalez Ramos, María del Carmen; Enz, Paula A.; Kowalczuk , Alicia; Galimberti, Ricardo (Revista del Hospital Italiano de Buenos Aires, 2008)
.